The Influences of Different Mixing Methods for Fungi and Substrates on the Mechanical and Physicochemical Properties of Mycelium Composites - Ziwei Dong; Dongyang Li; Yu Li; Shijun Xiao; Xuerong Han (Biology)
At present, the research on mycelium composites mainly focuses on the optimization of the preparation process, while the initial culture stage of the mixing method of fungi and substrates is often overlooked. This study is centered on exploring the impacts of different mixing methods on the appearance, mechanical properties, water absorption, and chemical and thermal decomposition characteristics of mycelium composites, aiming to identify a suitable mixing method. The experimental results show that different methods lead to significant differences in the mechanical properties of the materials. The compressive strength of the fungal inoculation group and the pre-culture group is ≥0.08 MPa, and the flexural strength is ≥11 N. The electron microscope results also confirm the effects of mycelium content and the interaction between mycelium and the matrix on the mechanical properties. The change range of the water absorption rate of the materials begins to increase at 30–60 min of immersion. After 60 min of immersion, the order of the water absorption rate is pre-culture < fungal inoculation < secondary inoculation. The mycelium membrane on the surface of the materials is beneficial for water resistance. The materials prepared by different methods have volume losses and similar thermal distributions, starting to degrade at approximately 170 °C and reaching maximum degradation at 350 °C. This study provides a reference for the optimization of the preparation of mycelium composites.